Motivational Processes Influencing Mental Health Among Winter Sports Athletes in China - Wu, Xinran; Zainal Abidin, Nor Eeza; Aga Mohd Jaladin, Rafidah (Frontiers in Psychology, 2021)
This study examined the association between motivational processes, psychological distress (depression, anxiety, and stress), and burnout among winter sports athletes within the Hierarchical Model of Intrinsic and Extrinsic Motivation (HMIEM). A total of 685 winter sport athletes participated in this study (377 males, 308 females, age range 18–25 years), from three sport universities across nine winter sports. They completed five psychometric inventories related to motivational factors and mental disorders. Overall, a task-oriented climate showed a positive association with basic psychological needs, eliciting a positive pathway to autonomous and controlled motivation. In contrast, an ego-oriented climate showed a negative association with basic psychological needs, eliciting a negative pathway to amotivation. Autonomous and controlled motivation were negatively associated with symptoms of psychological distress and burnout, while amotivation was positively associated with symptoms of psychological distress and burnout. These findings highlight the complex relationships between various motivational factors and mental health disorders among winter sport athletes, and support the essential requirement for adding mental health factors to the outcomes of the HMIEM sequence.